Cunqueiro in "El Pueblo Gallego" - Requeixo, Armando (Madrygal. Revista de Estudios Gallegos, 2016)
This paper aims to describe Alvaro Cunqueiro’s articles in El Pueblo Gallego (Vigo) before the outbreak of the Spanish Civil War. The texts are analysed in detail and organized according to a typology. Finally those that deal with themes related to Mondoñedo will be selected and reproduced. It should be stressed that Cunqueiro’s articles in El Pueblo Gallego are his most important series in pre-war press in terms both of the quantity and duration. He published more than fifty articles between mid-1933 and the beginning of the Civil War.